Nutritional programming improves dietary plant protein utilization in zebrafish Danio rerio - Kwasek, Karolina (PLoS One, 2020)
Nutritional Programming (NP) has been shown to counteract the negative effects of dietary plant protein (PP) by introducing PP at an early age towards enhancement of PP utilization during later life stages. This study explored the effect of NP and its induction time on growth, expression of appetite-stimulating hormones, and any morphological changes in the gut possibly responsible for improved dietary PP utilization. At 3 days post-hatch (dph) zebrafish were distributed into 12 (3 L) tanks, 100 larvae per tank. This study included four groups: 1) The control (NP-FM) group received fishmeal (FM)-based diet from 13–36 dph and was challenged with PP-based diet during 36–66 dph; 2) The NP-PP group received NP with dietary PP in larval stage via live food enrichment during 3–13 dph followed by FM diet during 13–36 dph and PP diet during 36–66 dph; 3) The T-NP group received NP between 13–23 dph through PP diet followed by FM diet during 23–36 dph and PP diet during 36–66 dph; and 4) The PP group received PP diet from 13–66 dph. During the PP challenge the T-NP group achieved the highest weight gain compared to control and PP. Ghrelin expression in the brain was higher in T-NP compared to NP-FM and NP-PP, while in the gut it was reduced in both NP-PP and T-NP groups. Cholecystokinin expression showed an opposite trend to ghrelin. The brain neuropeptide Y expression was lower in NP-PP compared to PP but not different with NP-FM and T-NP groups. The highest villus length to width ratio in the middle intestine was found in T-NP compared to all other groups. The study suggests that NP induced during juvenile stages improves zebrafish growth and affects digestive hormone regulation and morphology of the intestinal lining–possible mechanisms behind the improved PP utilization in pre-adult zebrafish stages.